ANALISIS SENGKETA HAK MILIK ATAS TANAH MENURUT TEORI TUJUAN HUKUM BERDASARKAN PUTUSAN MAHKAMAH AGUNG NO PERKARA 1597 K/PDT/2014 - AHMAD SAWARDI NIM. A1011151108 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract In this thesis, the author raises the problem of Analysis of Land Ownership Disputes Based on the Supreme Court's Decision Number 1597 K/Pdt/2014. The provision of guarantees of legal certainty in the land sector, first of all, requires the availability of complete and clear written legal instruments that are carried out consistently in accordance with the spirit of the provisions. Every land right that has been registered, a certificate will be issued by the land office located in each regency/city area, the legal force of the certificate is strong evidence, as long as it is not proven otherwise, the physical data and juridical data listed in the certificate must be accepted as data. correct as long as the data contained in the letter of measurement and the relevant land book.The formulation of the problem in this study is